Increased Serum Interleukin-34 Levels Are Related to the Presence and Severity of Cardiac Dysfunction in Patients With Ischemic Cardiomyopathy - Xi, Rui; Fan, Qin; Yan, Xiaoxiang; Zhang, Hang; Xie, Hongyang; Gu, Gang; Xu, Yan; Wang, Fang; Tao, Rong (Frontiers in Physiology, 2018)
Background: Several inflammatory factors have been demonstrated with diagnostic or prognostic value in patients with ischemic cardiomyopathy (ICM). Interleukin 34 (IL-34), an additional ligand of colony stimulating factor-1 receptor (CSF-1R), has been identified as a biomarker of coronary artery disease (CAD) and chronic kidney disease (CKD). However, the potential effect of IL-34 in ICM remains unknown. Methods: Serum IL-34 levels were detected in 360 subjects with ICM and in 465 subjects without ICM; the latter group included 233 controls without CAD and 232 patients with CAD and normal cardiac function. Uni- and multivariable logistic regression analyses were conducted to analyze the relationship between IL-34 and ICM. Results: IL-34 levels were significantly increased in patients with ICM compared with both groups of subjects without ICM (122.52 ± 115.30 vs. 95.02 ± 101.43 vs. 82.57 ± 84.24 pg/ml, respectively; P < 0.001). Moreover, serum IL-34 level was significantly positively correlated to NT-proBNP level (r = 0.223, P < 0.001), left ventricular end diastolic diameter and New York Heart Association (NYHA) functional class, indicating that a higher IL-34 level reflects more severe heart failure. Multivariable regression analyses revealed that IL-34 was remarkably associated with the presence and severity of ICM after adjusting for age, sex, conventional risk factors as well as medication (odds ratio (OR): 1.501, 95% confidence interval (CI): 1.249–1.803, P < 0.001, per SD increase). The predictive value of IL-34 value remained significant in patients already diagnosed with CAD. Conclusions: Increased IL-34 levels are relevant to the presence and severity of ischemic heart failure in all subjects and in patients with CAD. IL-34 may be used as a novel clinical biomarker of ICM with predictive value.